(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
We study the set of periods of the homogeneous polynomial maps f:R^n → R^n and f : C^n → C^n of degree m > 1. For these complex maps, we also describe the number of invariant straight lines through the origin by f^k for k = 1, 2, . . . and the dynamics of f^k over them.